Assessing flexibility options in power systems using Fuzzy Logic and AHP methods. (November 2022) - Alexopoulos, Dimitrios K.; Anastasiadis, Anestis G.; Kaminaris, Stavros D.; Vokas, Georgios A.; Psomopoulos, Constantinos S.
Abstract: In order to achieve high penetration of variable Renewable Energy Sources (vRES) in the power systems flexibility issues and needs inevitably arise. There are several flexibility options having a wide range of different technical and economic characteristics which meet the challenges posed by high penetration of vRES in the power systems. System operators seek to identify the most suitable flexibility options for the reliable operation of power systems. The aim of this research paper is to assess twenty-three (23) flexibility options in terms of energy management using three (3) technical characteristics (response time, efficiency, and storage duration) and three (3) economic characteristics (power capital cost, operation and maintenance cost and lifetime). For the assessment two different Multiple Criteria Decision-Making (MCDM) methods are used. A Fuzzy Decision-Making Tool (FDMT) under fuzzy rule-based system and fuzzy sets, using MATLAB software is developed and the Analytic Hierarchy Process (AHP) is applied. The results from the Fuzzy Logic and AHP methods show that demand side flexibility options are the most preferable flexibility options having, according to the FDMT, Fuzzy Preferability Index (FPI) 0.885 and, according to the AHP method, global priority vector 0.492. Demand side flexibility options are followed by Variable RE Power Plants (vRES) and Superconducting Magnetic Energy Storage (SMES), while Combined Heat and Power Plants (CHP), BioGas Power Plants (BGPP) and power to hydrogen and power to gas are the least preferable. The results from the FDMT and the AHP method are very useful especially in decision-makers because, after the assessment, they can take action to support and promote the most preferable flexibility options.